TRANSFORMASI KEPEMIMPINAN PERGURUAN TINGGI DAN JEJARING INTERNASIONAL - Bashori, Bashori; Vadhilla, Syukra (PRODU-Prokurasi Edukasi (Jurnal Manajemen Pendidikan Islam), 2019)
The issue of leadership becomes the study that never ends in every period. The leader is not only limited to being able to lead an organization, but the expected leader is a leader who is able to innovate and transform in finding solutions and developing a better organization. If quoting McGregor Burns' opinion, transformational leadership is a process in which leaders and followers together increase and develop their morality and motivation. In addition, a very brief but concise function that has been stated by the father of our education, Ki Hajar Dewantara, that a good leader must carry out functions, namely: "Ing Ngarso Sung Tulodo" (meaning in front of giving the role model); "Ing Madyo Mangun Karso" (meaning in the middle of creating work opportunities); "Tut Wuri Handayani" (meaning from behind gives encouragement and direction). This study is part of a theoretical concept that tries to examine the transformational leadership of higher education and the scope of mutually beneficial international networks.